2022
DOI: 10.3389/fimmu.2022.888897
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Interferon Response and Immune Hyperactivation in Severe COVID-19: Targeting STATs as a Novel Therapeutic Strategy

Abstract: A disease outbreak in December 2019, caused by a novel coronavirus SARS-CoV-2, was named COVID-19. SARS-CoV-2 infects cells from the upper and lower respiratory tract system and is transmitted by inhalation or contact with infected droplets. Common clinical symptoms include fatigue, fever, and cough, but also shortness of breath and lung abnormalities. Still, some 5% of SARS-CoV-2 infections progress to severe pneumonia and acute respiratory distress syndrome (ARDS), with pulmonary edema, acute kidney injury, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 148 publications
0
28
0
Order By: Relevance
“…Further, we observed that parental genes of the recurrent severe COVID-19-specific chimeric transcripts were significantly involved in interferon signaling. Recent studies showed that the dysregulated interferon response is crucial for the development of severe COVID-19 [ 69 , 70 ]. Interferon signaling induces the IFN-stimulated gene (ISG) expression by phosphorylating STAT1, and STAT1 phosphorylation was found to increase in severe COVID-19 cases, indicating an imbalanced JAK/STAT signaling and lack of ISG-induced transcription [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we observed that parental genes of the recurrent severe COVID-19-specific chimeric transcripts were significantly involved in interferon signaling. Recent studies showed that the dysregulated interferon response is crucial for the development of severe COVID-19 [ 69 , 70 ]. Interferon signaling induces the IFN-stimulated gene (ISG) expression by phosphorylating STAT1, and STAT1 phosphorylation was found to increase in severe COVID-19 cases, indicating an imbalanced JAK/STAT signaling and lack of ISG-induced transcription [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the dysregulated interferon response is crucial for the development of severe COVID-19 [ 69 , 70 ]. Interferon signaling induces the IFN-stimulated gene (ISG) expression by phosphorylating STAT1, and STAT1 phosphorylation was found to increase in severe COVID-19 cases, indicating an imbalanced JAK/STAT signaling and lack of ISG-induced transcription [ 69 ]. In this study, we observed that the cis-SAGe mechanism STAT1 gene generated a recurrent severe COVID-19 specific chimeric transcript.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chauss et.al showed that 1,25D promotes anti-inflammatory responses by switching off IFN-γ production from Th1 cells and upregulating IL-10 [ 43 ]. IFN-γ and IFN-β production is essential for effective viral clearance; viruses have mechanisms to evade the IFN responses, and severe COVID-19 is associated with dysregulation of IFN responses [ 44 , 45 , 46 ]. Down-regulation of IFN-β by vitamin D is associated with protection from inflammation in the lung following a virus infection with either influenza or SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Like other coronaviruses, SARS-CoV-2 employs various immune-escape strategies in order to limit competent IFN production and inhibit IFN signaling [ 21 ]. Four non-structural proteins (NSP) of SARS-CoV-2, including NSP13, NSP15, open reading frame (ORF) 7b, and ORF9b, have been reported to interact with host proteins involved in IFN signaling and impede IFN-1 mediated innate immune responses [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%